The Implications of Publisher Rights on The Digital Media Ecosystem From A Legal Perspective - Erwin Dede Nugroho; Juwita Juwita (International Journal Labs, 2026)
This research aims to analyze the limitations of existing copyright regulations (Law 28/2014, 40/1999, 32/2002) which create a regulatory vacuum on the inequality of publisher rights as well as the juridical implications of Presidential Regulation 32/2024 on the responsibility of digital platforms to support quality journalism. Using normative legal methods with legal, conceptual, comparative (Australia-EU) approaches, and triangulation of Rawls's theory, Lex Specialis (Manan), Suzor through qualitative literature studies. The results of the study show that Presidential Regulation 32/2024 as a lex specialis legitimately operationalizes publisher rights via distribution priority (Article 5), revenue sharing of Rp105 trillion (Article 7), the oversight committee of the Press Council (Articles 9-17), revolutionizing the platform capitalism into collaborative co-regulation. The novelty of the research lies in the first Rawls-Lex Specialis-Suzor Triangulation analyzing Presidential Decree 32/2024 as Indonesia's digital constitutionalism fills the gap in the conventional copyright literature against algorithmic governance.